طبعات الاختام على النصوص المسمارية - الياقوت بروج فالح مهدي (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
The function of the seal was not limited to proving ownership and possession only, as the seal had other functions, including sealing the goods to ensure that materials were not tampered with, sealing the doors of houses and stores. Later several important functions were added to it, including the sealing of cuneiform texts (the mud tablets) the subject of our research as it proved the legitimacy of administrative transactions. It is considered a kind of protection against forgery, in addition to its importance in controlling dates, as it is considered a basic criterion after pottery to control the dates of strata in archaeological sites. The use of seals in sealing the clay figures or their covers appeared in the late third millennium BC, as many of these editions appeared in texts from the third Ur era and became more common in the second millennium BC. and beyond.